2021
DOI: 10.1177/08850666211066892
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in a Tertiary Pediatric Cardiac Intensive Care Unit: Risk Factors and Outcomes

Abstract: Objective Delirium is an increasingly recognized hospital complication associated with poorer outcomes in critically ill children. We aimed to evaluate risk factors for screening positive for delirium in children admitted to a pediatric cardiac intensive care unit (CICU) and to examine the association between duration of positive screening and in-hospital outcomes. Study design Retrospective cohort study in a single-center quaternary pediatric hospital CICU evaluating children admitted from March 2014-October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 52 publications
0
13
1
Order By: Relevance
“…Two studies found that older age was associated with PD, that is, in children 2-5 years old (29) and in children greater than or equal to 12 years old (38). However, overall we did not find an association between age under 2 years and greater odds of PD in the pooled analysis (OR 2.01 [95% CI 0.69-5.88]) (24,25,30,32,36,37,41,43).…”
Section: Patient-related Factorscontrasting
confidence: 65%
See 3 more Smart Citations
“…Two studies found that older age was associated with PD, that is, in children 2-5 years old (29) and in children greater than or equal to 12 years old (38). However, overall we did not find an association between age under 2 years and greater odds of PD in the pooled analysis (OR 2.01 [95% CI 0.69-5.88]) (24,25,30,32,36,37,41,43).…”
Section: Patient-related Factorscontrasting
confidence: 65%
“…1 ). Thus, 24 articles (22–45) were included in our detailed analyses. The characteristics of the 24 pediatric cohort studies are summarized in Supplemental Digital Content 3 (http://links.lww.com/PCC/C331).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) Despite knowledge that ICU care bundles similar to PICU Liber8 bundle can hasten liberation from mechanical ventilation and the ICU while improving patient outcomes (5-7), implementation in PICUs remain variable. National guidelines recommend implementing such bundles ( 8), yet, significant barriers derail successful implementation and/or sustainability, even for those who want it (9). The key strength of the work by Jones et al (2) is their low cost, simple, effective, and feasible tool, which could be adapted for all…”
mentioning
confidence: 99%